Anoxic photo-oxidation of Mn(II)-bearing carbonates on Mars and early Earth - Jiye Guo; Yuke Zhu; Nicholas J. Tosca; Lu Pan; David C. Catling; Yi Liu; Wenhua Zhang; Amrit S. Chaddha; Pengcheng Ju; Jie Li; Zongbin Zhang; Anya Huo; et al. (Proceedings of the National Academy of Sciences, 2026)
Manganese oxides, thought to form almost exclusively through reactions between Mn 2+ and O 2 , catalyze oxidative transformations among redox-sensitive metals. Thus, the occurrence of Mn oxides, either observed or inferred from sedimentary geochemical data, has formed the basis for multiple hypotheses concerning the evolution of the atmospheric redox state on the early Earth and Mars. Here, using theory and experiments, we report that the band gap of common Ca/Mg carbonate minerals (including calcite, magnesite, and aragonite) is significantly lowered by trace incorporation (0.8 wt% or lower) of Mn(II) into their bulk structure or surface, conferring photochemical reactivity under ultraviolet conditions relevant to early Earth and Mars (200 to 400 nm). Moreover, we show that surface incorporation of Mn(II) reduces the fundamental band gap much more effectively (by >1 eV) than bulk incorporation. Our results suggest that photo-oxidation of Mn(II)-bearing carbonates could have occurred widely on planetary surfaces, resulting in the abiotic formation of manganese oxides without free molecular oxygen. Photochemically driven redox cycling of manganese could help sustain redox disequilibria for microbial metabolisms, but compromises the use of manganese oxides as oxygen barometers.